Special Educator Self-Efficacy: The Impact of Training and Experience - Johnson, Sarah Robbie; Jones, David R. (Educational (Re)naissance, 2021)
In California, the longstanding insufficiency of special educators has compounded since the 2013-2014 academic year. Districts and state legislators have relied on the issuance of substandard permits (i.e., Provisional Intern Permits, Short-Term Staff Permits, and Intern Credentials) to counteract the shortage. However, the effectiveness of this approach has limited evaluation. This study evaluated differences between pre-service and in-service special educators’ self-efficacy ratings. Special educators serving in California’s Central Valley on substandard permits or valid teaching credentials (i.e., Preliminary and Clear Credentials) completed the Teachers’ Sense of Efficacy Scale. Differences were assessed across several variables using independent t-tests and one-way ANOVAs. Significant differences emerged in special educators’ self-reported levels of self-efficacy as a function of credential status, favoring those with valid credentials. The findings indicate a correlation between special educators’ credential status (a proxy for training) and self-reported self-efficacy. The results of this study add to the research on special educators’ self-efficacy by exploring the phenomenon among a newly emerged group of California-based special educators: substandard permit holders. keywords: self-efficacy, special education, substandard authorization, pathways to teaching